Prinsip-Prinsip Hukum Islam dalam Peraturan Daerah: Melacak Motivasi dan Efektifitas Perda Bernuansa Syariah di Pamekasan - Maimun Maimun; Ainul Haq (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2018)
The presence of several Regional Regulations (Perda) with shari'a nuance in Pamekasan is expected to make his community more behave Islam . But the lofty desire has not been fully realized according to the ideals of its formation. This research tries to find out what exactly is behind the (motivation) of the issuing of Regional Regulations with shari'a nuance in Pamekasan, and how is the effectiveness of applying Regional Regulations with shari'a nuance in Pamekasan . Through a qualitative - phenomenological approach with the type of field research and descriptive analysis of Miles model and Huberman, it produced some findings: First, the motivation behind the establishment of Regional Regulations with shari'a nuance was not only because of heir philosophical-sociological and juridical elements but also the existence of motives of identity politics integrated with law politics . Second , the implementation of Regional Regulations with shari'a nuance has not been maximum and effective in forming the behavior of Pamekasanese society more Islamic. Many factors that made the problem emerge, neither because of many regional regulations that their enforcement were ignored in the field nor because of the presence of the regional regulations that were contradictory with other regional regulations.Hadirnya beberapa Peraturan Daerah (perda) yang bernuansa syari’ah di Pamekasan diharapkan mampu menjadikan masyarakatnya lebih berperilaku Islâmî. Namun keinginan luhur tersebut belum sepenuhnya terwujud sesuai cita-cita pembentukannya. Penelitian ini mencoba mencari tahu apa sebenarnya yang melatarbelakangi (motivasi) terbitnya perda-perda bernuansa syari’ah di Pamekasan?, dan bagaimana efektivitas penerapan perda-perda bernuansa syari’ah di Pamekasan?. Melalui pendekatan kualitatif-fenomenologis dengan jenis penelitian lapangan, dilakukan langkah analisis deskriptif model Miles dan Huberman, dihasilkan temuan pertama bahwa motivasi di balik pembentukan perda bernuansa syari’ah di Pamekasan di samping karena adanya unsur filosofis-sosiologis dan yuridis, juga adanya motif politik identitas yang berkelindan dengan politik hukum. Kedua penerapan peraturan daerah yang bernuansa syari’ah belum maksimal dan belum efektif membentuk perilaku masyarakat Pamekasan yang lebih Islâmî, banyak factor yang menyebabkan, baik karena banyak peraturan daerah yang terabaikan penegakannya di lapangan, maupun karena kehadiran peraturan daerah tersebut yang kontra produktif dengan peraturan daerah yang lain.